AI IN EDUCATION AND SKILL DEVELOPMENT - Anuja Mishra; Rakesh Kumar Sharma (International Educational Journal of Science and Engineering, 2025)
Artificial Intelligence (AI) is fundamentally transforming education and skill development by enabling personalized, scalable, and adaptive learning experiences through Intelligent Tutoring Systems (ITS), AI-powered platforms, and immersive technologies like Virtual and Augmented Reality. ITS leverage AI to mimic one-on-one tutoring by dynamically adapting content, pacing, and feedback based on individual learner profiles, enhancing engagement and outcomes across diverse academic and professional domains. AI-based platforms such as Coursera and edX provide accessible, flexible education with customized learning paths and real-time support, democratizing access worldwide. Moreover, AI facilitates workforce readiness by identifying skill gaps and delivering tailored upskilling programs, fostering lifelong learning and economic adaptability. However, challenges including data privacy, algorithmic bias, digital divides, and ethical considerations require vigilant governance and inclusive strategies. This study underscores AI’s potential to revolutionize education and training while emphasizing the necessity for responsible implementation to ensure equity, transparency, and broad societal benefit.